Adaptation of business and consumers to modern challenges in Ukraine - Bila, Iryna; Zakrevska, Lyudmila; Kovalchuk, Inna; Tkachenko, Olga; Shevchenko, Olena (My University, 2023)
Досліджені фактори, що впливають на рівень адаптації бізнесу та споживачів. Встановлено, що адаптаційні процеси мають диференційований, нерівно мірний і несталий характер, вказані причини цього. Указано, що вплив сукупності загроз може мати адитивний і мультиплікативний характер. Указано, що ефективне адаптування підприємств можливе лише за інтеграції зусиль менеджменту підприємств і державних інституцій. Запропоноване запровадження державної Стратегії сприяння адаптації бізнесу та споживачів. Наукова новизна. Розроблена математична модель поточного оцінювання рівня адаптації. Розроблена математична модель дозволяє оцінити дотримання напряму адаптації та більш релевантним чином провадити оперативне планування діяльності підприємства.

Factors affecting the level of business and consumer adaptation were studied. It is established that adaptation pro cesses have differentiated, uneven and unstable character and reasons for this are indicated. It is indicated that the impact of set threats can be additive and multiplicative in nature. It is indicated that effective adaptation of enterprises is possible only with the integration of efforts by management of enterprises and by state institutions. It is proposed to introduce the State Strategy for Fa cilitating the Adaptation of Businesses and Consumers. Originality. A mathematical model of the current assessment of the level of adaptation is developed. Practical value. The developed mathematical model makes it possible to assess compliance with the direction of adaptation and conduct operational planning of the enterprise in a more relevant manner.
Keywords: level of adaptability; mathematical model; strategy for support adaptation; кафедра економіки і права; адаптація бізнесу; математична модель; стратегія сприяння адаптації